a arca totok kerot: CREATION OF THE ARCA TOTOK KEROT BATIK MOTIFS APPLIED TO EVENING GOWN - Muhammad Arif Jati Purnomo; Sulistiana Etika (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Abstract The final assignment for this work is entitled "Creation of the Arca Totok Kerot Batik Motif Applied to Evening Gowns", which is a work inspired by the story of the Arca as a princess of Lodoyo Blitar, who had a brave nature and was determined to meet the king of Kediri to express her feelings that he had feelings for the king but on his way he was killed because he was involved in a war. The king, who just found out that the princess had come to meet him, made a memento in the form of a statue as a form of respect. The aim of this final project is to create a Totok Kerot statue motif and apply it to an evening gown. The method used consists of three stages, six steps, namely from the exploration, design and realization stages starting with observing the Arca website, social media, literature studies and conducting data mining through interviews. The second stage is designing the motif by using all the data as a reference for creating alternative sketches which will later be selected as the selected design. The third stage is the embodiment technique, namely realizing the selected design into a real work. The creation of the work begins with the process of making patterns, scratching, batiking, coloring, sewing, sewing and finishing. The works created in this final project are 4 evening gowns, each of which has a title and implied meaning. The creation of the work resulted in four motifs with the titles: 1. Smaradahana, 2. Ceplok Branta, 3. Liris Diraya, 4. Danumaya. And produced four evening gowns with the titles: 1. Anindya, 2. Bathari, 3. Gayatri, 4. Laksmi. This design produces fashion works targeted at adult women from the ages of 18 to 40 years. Key word : Arca Totok Kerot, Batik, Gaun malam